Croissance, engraissement et cycle sexuel de Crassostrea gigas dans le Bassin d'Arachon: comparaison des huîtres agées de 1 et 2 ans - Maurer, Daniele; Borel, Michel (Actes du colloque, Wimereux, 4-8 novembre 1985, Haliotis 15, pp 125-134, 1985)
Two-year-old oysters have a physiology which is reproduction-oriented, their maturation occurring synchronously among oysters from the same batch. The importance of the spring accumulation of glycogenated stocks varies through the years and correlates with the growth stage. Glucidic components are quickly used during the month preceding egg-laying and are transformed into lipid stocks for the oocytes. One-year-old oysters develop at different rates, some of them not showing any sign of maturation and the percentage of laying individuals varies through the years. Glycogenated stocks accumulate in a similar way in both age-classes and their more precocious and more intense use by young molluscs is not necessarily linked with their gametogenesis and growth, although one could assume that their metabolic needs are more important during this stage. Young oysters would find it difficult to adapt to spring temperature rises resulting in a decrease in the amount of food available. The obtained results are discussed in relation with the summer mortalities impacting essentially one-year-old oysters in the Arcachon Bay. Les huîtres âgées de 2 ans ont une physiologie orientée vers la reproduction, la maturation s'effectuant de façon synchrone dans un même lot. L'importance de l'accumulation printanière de réserves glycogènées est variable selon les années et corrélative de la phase de croissance. Les composants glucidiques sont rapidement utilisés au cours du mois précédent la ponte, et transformée en lipides de réserve des ovocytes. Les huîtres âgées de an évoluent à des rythmes différents, certaines ne présentant aucun signe de maturation; le pourcentage de sujets qui fraient varie selon les années. Les réserves glycogènées s'accumulent de façon comparable chez les 2 classes d'âge; leur utilisation plus précoce et plus Intense par les jeunes mollusques n'intervient pas nécessairement en liaison avec la gamétogénèse et la croissance. et laisse supposer des besoins métaboliques plus importants à cette période. Les jeunes ...